(untitled) (Al-Academy, 2015)
Between decline and appearing dichotomy, art history comes to announce birth of an era that glories past and find new names that are emerged from yearning to past and represented by neo-classical, By refusing the previous approaches and create topics that touché culture and derived from it through s revitalizing ideal beauty standards. One of neo-classical artists, who tried to simulate the classical works, is (Jean-Auguste-Dominique Ingres), who put framework for semantic aesthetic of the art form by revitalizing past glories and deeply searching myths and cultures through finding special artistic features that emphasizes artist own stylistics and identity. This research studies artistic features of women form in (Jean-Auguste-Dominique Ingres) works as he occupied a distinct space in global configuration, cannot be underestimated or neglected. He was marked by his interest to implement variant topics that are related to women. Hence, the study introduced women form in his works and then revealing some of their features, accordingly this paper consists of four chapters: The first comprises paper problem through rising the following questions: 1.Does the artist (Ingres) experience has artistic features distinct women form in his works?2.What is the environment impact in guiding artist style and determining women form features? The second chapter includes theoretical framework and comprises three topics: high-class women, women form in topics with myth characteristic, and Eastern women. The third chapter comprises paper procedures, While The fourth chapter was devoted to show researcher results according to paper objectives